1975
DOI: 10.1111/j.1468-2958.1975.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF DOMINANCE TENDENCIES ON FLOOR HOLDING AND INTERRUPTION BEHAVIOR IN DYADIC INTERACTION1

Abstract: Eighteen dyads (1 0 female and eight male), each composed so as to have one member who scored high and one who scored low on a test of personality dominance, were given a cooperative problem-solving discussion task lasting fifteen minutes. The persons with the more dominant personalities held the floor more and attempted more interruptions in proportion to their partners' total amounts of speaking time than did those with less dominant personalities. There was also evidence that the high dominant subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Zimmerman and West felt that the differences among cross-sex dyads were reflections of the power and dominance enjoyed by men in society, and in a subsequent study (West and Zimmerman, 1977) found the same sort of marked asymmetry in rates of interruptions among adult-child dyads, thereby giving further credence to the idea that the differences were tied to status. The notion that interruptions are a form of dominance is also supported in the work of Courtright et al (1979), Eakins and Eakins (1978), Rogers and Jones (1975), and West (1984).…”
Section: Conversational Division Of Labormentioning
confidence: 70%
“…Zimmerman and West felt that the differences among cross-sex dyads were reflections of the power and dominance enjoyed by men in society, and in a subsequent study (West and Zimmerman, 1977) found the same sort of marked asymmetry in rates of interruptions among adult-child dyads, thereby giving further credence to the idea that the differences were tied to status. The notion that interruptions are a form of dominance is also supported in the work of Courtright et al (1979), Eakins and Eakins (1978), Rogers and Jones (1975), and West (1984).…”
Section: Conversational Division Of Labormentioning
confidence: 70%
“…It is often presupposed in sociological and social psychological studies of Interruption that the phenomenon is intrinsically bound up with the establishment of control or dominance in discourse (Rogers and Jones, 1975;West andZimmerman, 1977, 1983;West, 1979;Dindia, 1987). But one notable feature of many investigations along these lines is their failure to explicitly differentiate between incursive utterances which are 'interruptive' sequentially speaking, but which may well be in some v/ay cooperative interactionally speaking, and those which are interruptive in both sequential and interactional terms -that is, in which a Speaker is doing 'control', or 'dominance', or 'being hostile', or 'being argumentative'.…”
Section: Resultsmentioning
confidence: 99%
“…For example, men typically view verbal exchanges as an opportunity to &dquo;... protect themselves from others' attempts to put them down&dquo; (p. 25). Although a few exceptions exist (see Kimble, Yoshikawa, &Zehr, 1981, andJones, 1975), research indicates that men are more likely to change the course of a dyadic relationship through the use of interruptions (Eakins & Eakins, 1976;Zimmerman & West, 1975), by determining the discussion topic (Wiley & Wooley, 1988), by exerting control over the interaction (Fishman, 1983;Spencer & Drass, 1989), and by doing most of the talking (Swacker, 1975). With respect to the pre-7-1 sent study, this control may manifest itself by males using more dominant behaviors to change the flow of the discussion by abruptly changing topics.…”
Section: Communication Patterns In Dyadic Relationshipsmentioning
confidence: 97%